Role of PROPELLER-DWI of the prostate in reducing distortion and artefact from total hip replacement metalwork. Issue 102 (May 2018) - Czarniecki, Marcin; Caglic, Iztok; Grist, James T.; Gill, Andrew B.; Lorenc, Kamil; Slough, Rhys A.; Priest, Andrew N.; Barrett, Tristan
Abstract: Objective: To compare image quality, artefact, and distortion in standard echo-planar imaging (EPI) with periodically rotated overlapping parallel lines with enhanced reconstruction (PROPELLER) for prostate magnetic resonance imaging (MRI) diffusion-weighted imaging (DWI) in patients with previous total hip replacement (THR). Methods: 21 male subjects with a clinical suspicion for, or known prostate cancer and previous THR were scanned at 1.5 T using a phased-array body coil. DWI was obtained using single-shot EPI and PROPELLER techniques using fat saturation (PROPELLER-DWI-FS), and without (PROPELLER-DWI-NFS). Image quality (the overall impression of diagnostic quality) was compared to T2 -weighted (T2WI) imaging using a 5-point Likert scale, with diffusion sequences additionally scored for artefact and distortion according to a 4-point scale, with artefact defined as the amount of prostate affected and distortion as the degree of warping of the organ. The T2W and DW image volumes were compared to produce quantitative distortion maps. A two-sample Wilcoxon test compared the qualitative scores, with inter-reader variability calculated using Cohen's kappa. Results: 21 patients were included in the study, with an average age of 70.4 years and PSA 9.2 ng/ml. Hip metalwork was present bilaterally in 3 patients, left-sided in 9, and right-sided in 9. PROPELLER-DWI-FS significantly improved image quality (p < 0.01) and reduced distortion (p < 0.01) when compared to standard EP-DWI. Artefact was not shown to be significantly improved. The last 5 patients in the study were additionally imaged with PROPELLER-DWI-NFS, which resulted in a significant reduction in artefact compared to EP-DWI (p < 0.05). Quantitative distortion was significantly lower compared to EP-DWI for both PROPELLER with fat saturation (p < 0.01) and without fat saturation (p < 0.01). Conclusion: PROPELLER-DWI demonstrates better image quality and decreases both artefact and distortion compared to conventional echo planar sequences in patients with hip metalwork.